2019
DOI: 10.3345/kjp.2018.06842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effectiveness of growth hormone therapy according to disease-causing genes in children with Noonan syndrome

Abstract: Purpose To analyze the growth response to growth hormone (GH) therapy in prepubertal patients with Noonan syndrome (NS) harboring different genetic mutations. Methods Twenty-three patients with prepubertal NS treated at Pusan National University Children’s Hospital between March 2009 and July 2017 were enrolled. According to the disease-causing genes identified, the patients with NS were divided into 4 groups. Three groups were positive for mutations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Numerous studies have reported increased height SDS and growth velocity with rhGH therapy [ 12 - 16 ]. Osio et al [ 17 ] reported improved final height outcomes in patients with NS, including a change in height SDS of 1.7 and mean height gain of 13 cm in boys and 9.8 cm in girls after 7.5 years of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported increased height SDS and growth velocity with rhGH therapy [ 12 - 16 ]. Osio et al [ 17 ] reported improved final height outcomes in patients with NS, including a change in height SDS of 1.7 and mean height gain of 13 cm in boys and 9.8 cm in girls after 7.5 years of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al [ 13 ] reported that the height SDS in patients without PTPN11 mutations was significantly greater than that in patients with PTPN11 mutations after 3 years of rhGH therapy. However, Jo et al [ 12 ] reported that the growth velocity in patients with PTPN11 mutations was greater than that in patients without mutations in NS-related genes. Malaquias et al [ 22 ] reported that patients without PTPN11 mutations showed a poor response to rhGH therapy compared to patients with PTPN11 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies that have reported long-term results on the efficacy of rhGH treatment in NS (34)(35)(36). Recently, in two complementary non-interventional studies, NordiNet ® IOS and ANSWER, it has been demonstrated that NS children treated with rhGH achieved significant height gain during the first 3 years of follow-up (37).…”
Section: Discussionmentioning
confidence: 99%
“…Binder [11] demonstrated a trend toward a higher first-year growth rate in prepubertal NS children without the PTPN11 mutation. In this regard, the study of Jo et al [12] is considered valuable because it compared early GH effects in prepuberty between patients with and those without NS-causing gene mutations. The association between shortterm growth response and genotype seems unsuitable for an analysis of GH effect in NS [8,13].…”
mentioning
confidence: 99%
“…Heterozygous mutations in more than 17 genes are known to underlie NS or NS-related disorders. In the study of Jo et al [12], the response to GH therapy of NS children in PTPN11, RAF1 , and SOS1 mutation groups were compared to those of NS patients in 5 genes ( PTPN11, RAF1, SOS1, KRAS , and BRAF ) undetected (FGU) group. There are several problems with organizing patients with NS without mutations in 5 genes into the FUG group, as patients in the FGU group may have other undetected NS-causing genes.…”
mentioning
confidence: 99%